PENGEMBANGAN RUBRIK PENILAIAN PORTOFOLIO PROSES SAINS SISWA PADA MATERI EKOSISTEM - Widyaningsih, Vera; Endang Susilowati, Sri Mulyani; Rudyatmi, Ely (Journal of Biology Education, 2013)
Purpose of this study was to develop portofolio assessment rubrics of studentscientific processes on ecosystems. This study was Research and Development, using One Shot Case Study experimental design for its field-testing. The samples of this study were 135 yunior secondary school students (class VIIA, VIIB, VIIC, and VIIG). Research steps were as follows: problems and potential identification, data collection, product design, validation, field-testing and final production. Data were collected from (1) eligibility of portfolio assessment rubric of student scientific processes on ecosystems, (2) final scores of portfolios, and (3) student and teacher responses. Data was analyzed by descriptive percentages. ANOVA was used to identify the different average of portfolio scores.Â  The results showed that portofolio assessment rubrics could be used to assess students scientific processes on ecosystem. The average assessment scores from experts to the portfolio assessment rubrics of studentsâ scientific processes on ecosystem were 99.07% (very appropriate). The average assessment scores of Â portfolio class VIIC during field testing were 73,47. Average scores of portfolio was follows: 75,56 (VIIA), 76,17 (VIIB), and 76,51 (VIIG). ANOVA test showed the average assessment of portfolio was not significantly different from other three the groups. A portfolio assessment was reliable or rubrics could be used well.Â  Student and teacher responses to portofolio assessment rubrics of studentsâ scientific processes on ecosystems was very good. The conclusions of this study was that the develop portofolio assessment rubrics of studentsâ scientific processes on ecosystem was able to be used for SMPNegeri 1 Wedarijakasa.Â Penelitian ini bertujuan untuk mengembangkan rubrik penilaian portofolio proses sains siswa materi ekosistem. Penelitian merupakan Research and Development, desain eksperiment menggunakan one shot case study. Sampel penelitian yaitu siswa kelas VIIA, VIIB, VIIC dan VIIG berjumlah 135 siswa. Langkah-langkah penelitian meliputi analisis potensi dan masalah, pengumpulan data, desain produk, validasi desain, uji coba produk, uji coba pemakaian dan produk final. Data penelitian berupa kelayakan rubrik penilaian portofolio proses sains siswa materi ekosistem, nilai portofolio, tanggapan siswa dan guru. Data dianalisis secara deskriptif persentase. Ada atau tidaknya perbedaan rata-rata nilai portofolio diuji menggunakan ANAVA. Hasil penelitian berupa rubrik penilaian portofolio proses sains siswa materi ekosistem. Rubrik penilaian portofolio proses sains siswa materi ekosistem sangat layak, nilai rata-rata kelayakan 99,07%. Rata-rata nilai portofolio kelas VIIC pada uji coba awal 73,47. Rata-rata nilai portofolio kelas VIIA, VIIB, dan VIIG pada uji coba pemakaian adalah 75,56 ; 76,17 dan 76,51. Hasil uji ANAVA rata-rata nilai portofolio tidak berbeda secara nyata atau ajeg. Tanggapan siswa dan guru terhadap rubrik penilaian portofolio proses sains sangat baik. Simpulan penelitian telah dihasilkan rubrik penilaian portofolio proses sains siswa yang layak dan baik digunakan pada materi ekosistem di SMPN 1 Wedarijaksa.